Molecular Characterization of Begomoviruses and DNA Satellites Associated with a New Host Spanish Flag (Lantana camara) in India. (7th December 2013) - Marwal, Avinash; Kumar Sahu, Anurag; Gaur, Rajarshi Kumar
Abstract : In the year 2010 yellowing of leaf vein disease was observed on Spanish Flag ( Lantana camara ) in Sirsa, Haryana province, India. There was no earlier report of association of begomovirus and DNA satellites with Lantana camara . Therefore, molecular characterization and understanding of the genomic analysis of begomovirus infecting Lantana camara is imperative for the pathogen diagnosis and disease management. This is the first report and molecular characterization of a begomovirus associated with its two satellites infecting a new host Lantana camara in India.